2023
DOI: 10.1021/acsnano.2c09255
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Modified Polyethyleneimine Nanoparticles for Enhancing the Carboxylation Reaction and Plants’ CO2Uptake

Abstract: Increasing plants' photosynthetic efficiency is a major challenge that must be addressed in order to cover the food demands of the growing population in the changing climate. Photosynthesis is greatly limited at the initial carboxylation reaction, where CO 2 is converted to the organic acid 3-PGA, catalyzed by the RuBisCO enzyme. RuBisCO has poor affinity for CO 2 , but also the CO 2 concentration at the RuBisCO site is limited by the diffusion of atmospheric CO 2 through the various leaf compartments to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…It is a conical shape carbon nanostructure [42][43][44]. CNHs provide alternative of CNTs in wide range of applications such as energy conversion, drug delivery, gas storage and supercapacitors etc.in contrast to CNTs they differ in following ways such as absence of metallic catalyst in their synthesis and their mass production at room temperature [21,63,64]. CNHs can be synthesized by sufficient injection of energy to vaporize and differ from synthesis of CNTs.…”
Section: Carbon Nanohorns(cnhs)mentioning
confidence: 99%
“…It is a conical shape carbon nanostructure [42][43][44]. CNHs provide alternative of CNTs in wide range of applications such as energy conversion, drug delivery, gas storage and supercapacitors etc.in contrast to CNTs they differ in following ways such as absence of metallic catalyst in their synthesis and their mass production at room temperature [21,63,64]. CNHs can be synthesized by sufficient injection of energy to vaporize and differ from synthesis of CNTs.…”
Section: Carbon Nanohorns(cnhs)mentioning
confidence: 99%
“…Some researchers reported that the concentration of CO 2 between plant leaf cells increased while promoting a significant increase in carboxylation efficiency (CE) [36,37]. The increase in carboxylation reaction efficiency showed that the storage of photosynthetic substances was accelerated, promoting reproductive growth, promoting photosynthesis in wheat plants, improving the transport of photosynthetic substances in the body, and promoting the synthesis and transport of organic compounds [38,39].…”
Section: Carboxylation Efficiency (Ce) and Plr Curve In Response To H...mentioning
confidence: 99%
“…Tailormade nanomaterials that were incorporated directly in plants apparatus enabled the development of environmental sensors. , The plant was acting as the sampler and concentrator of analytes while the nanomaterials produced a readable output. Functional nanomaterials can also enhance plant processes for example photosynthesis and CO 2 uptake or even give new capabilities to plants such as light emission. , Plants, being natural energy converters that transform sunlight to chemical energy, have also been the focus of biohybrid energy devices. Biofunctionalized electrodes integrated into the plant tissue can convert sugars and oxygen produced by photosynthesis into electricity. , Additionally, plants’ natural movements and leaves’ dielectric properties have been combined with artificial leaves for triboelectric generators that produce sufficient energy to power low consumption electronics. , Our group, on the other hand, demonstrated energy storage in plants via in vivo organization of conducting materials in their tissue that can act as charge storage electrodes in biohybrid supercapacitors …”
Section: Introductionmentioning
confidence: 99%